FORMULASI KEBIJAKAN SYARI’AH (STUDI KASUS PERATURAN DAERAH NOMOR 07 TAHUN 2012 TENTANG BISA BACA DAN TULIS AL-QUR’AN BAGI MURID SEKOLAH YANG BERAGAMA ISLAM) - Kesumagiri, Heru Andhika; Marta, Auradian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was motivated by the problems of school-age children irregularities that occurred as a result of globalization have followed and negatively affect social order, especially school-age children Indragiri Hilir. The system of regional autonomy that gives the rights, powers and obligations of autonomous regions to set up and manage their own affairs and interests of the community both in terms of regional development and the setting order of a society, in which case through the initiative right of Parliament, Commission IV DPRD charge of the issue of education show a sense of responsibility to make regulations and signs the management and delivery of education is much higher quality.By using qualitative research methods, that is by explaining, describing the results of research to describe an event and process as well as the particular circumstances of the data collecting research using data collection techniques such as literature study to undertake a study of the literature-literature relating to the title of the research, interviews ( interviews) in order to gather information through communication debriefing against informants or respondents of this study, and by doing penulusaran documentation to documents relating to aspects of the study and then the data were analyzed by classifying, describing, examine the data for later described and presented in descriptive form in order to complete the scientific work in the form of the title of this research thesis.The results of this study, obtained by the process of policy formulation on Can Read Write Qur'an long enough from planning Ranperda since 2010 with obstacles such, the exclusion of Ranperda Can Read Write Koran on a scale of priorities in 2010 and the lack of the substance contained in Ranperda Can Read Write Qur'an in 2011. then Ranperda Can Read Write Qur'anic back proposed and the continuation into Ranperda Planning for later discussion together with the executive and legislative in 2 (two ) level talks which I and II level talks to be prescribed and enacted into sheets Indragiri Hilir regency in 2012.Keywords: Policy Formulation, Regional Regulations, Can Read Write Qur'an